2000
DOI: 10.1089/08927790050152177
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Retroperitoneoscopic Partial Adrenalectomy Using Ultrasonic Scalpel for Aldosterone-Producing Adenoma

Abstract: Posterior retroperitoneoscopic partial adrenalectomy using the ultrasonic scalpel may be a valuable treatment for typical solitary APA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 9 publications
1
11
0
1
Order By: Relevance
“…Eight patients were normotensive and the other two required less antihypertensive medication on follow-up. This report [15] confirmed that retroperitoneal LPA is a valuable alternative to the transperitoneal approach in the treatment of the solitary APA.…”
Section: Adrenal Adenomasupporting
confidence: 80%
See 1 more Smart Citation
“…Eight patients were normotensive and the other two required less antihypertensive medication on follow-up. This report [15] confirmed that retroperitoneal LPA is a valuable alternative to the transperitoneal approach in the treatment of the solitary APA.…”
Section: Adrenal Adenomasupporting
confidence: 80%
“…In another study, Sasagawa et al [15] performed posterior retroperitoneal LPA on 10 patients. The mean blood loss was minimal, and although subcutaneous emphysema occurred in three patients there were no serious operative complications.…”
Section: Adrenal Adenomamentioning
confidence: 99%
“…Adrenal-sparing surgery using the posterior retroperitoneoscopic approach has also been reported [19,25]. In the series reported by Walz et al [25], 11 of the 22 cases operated on were for primary hyperaldosteronism.…”
Section: Discussionmentioning
confidence: 99%
“…All the patients were cured at a mean follow-up of 11 months. In another series, Sasagawa et al [19] reported 10 patients with aldosterone-producing adenomas who underwent posterior retroperitoneoscopic partial adrenalectomy. The adenomas were dissected using the ultrasonic scalpel with no serious operative complications.…”
Section: Discussionmentioning
confidence: 99%
“…Weitere Autoren berichteten bei kleineren Fallzahlen von ähnlichen Opertionstechniken und übereinstimmend von der postoperativen Normotension und Normokaliämie der Patienten bei keinem Rezidiv bzw. Persistenz des Hyperaldosteronismus [1,10,11,12,18].…”
Section: Diskussionunclassified